Quality of life and functional outcome after infravesical desobstruction and HIFU treatment for localized prostate cancer. Issue 1 (December 2017) - Hatiboglu, G.; Popeneciu, I.; Deppert, M.; Nyarangi-Dix, J.; Hadaschik, B.; Hohenfellner, M.; Teber, D.; Pahernik, S.
Abstract Background To evaluate quality of life, functional and oncological outcome after infravesical desobstruction and HIFU treatment for localized prostate cancer. Methods One hundred thirty-one patients, treated with TURP and HIFU in a single institution were followed up for oncological and functional outcome. Oncological outcome was quantified by biochemical recurrence free survival using the Stuttgart and Phoenix criteria. Quality of life was assessed by usage of standardized QLQ-C30 and QLQ-PR25 questionnaires. In addition, functional questionnaires such as IPSS and IIEF-5 were used. Complications were assessed by the Clavien-Dindo classification. Results One hundred thirty-one patients with a mean age of 72.8 years (SD: 6.0) underwent HIFU for prostate cancer (29.0% low risk, 58.8% intermediate risk, 12.2% high risk). PSA nadir was 0.6 ng/ml (SD: 1.2) after a mean of 4.6 months (SD: 5.7). Biochemical recurrence free survival defined by Stuttgart criteria was 73.7%, 84.4% and 62.5% for low-, intermediate- and high-risk patients after 22.2 months. Complications were grouped according to Clavien-Dindo and occurred in 10.7% (grade II) and 11.5% (grade IIIa) of cases. 35.1% of patients needed further treatment for bladder neck stricture. Regarding incontinence, 14.3%, 2.9% and 0% of patients had de novo urinary incontinence grade I°, II° and III° and 3.8% urge incontinence due to HIFU treatment. Patients were asked for the ability to have intercourse: 15.8%, 58.6% and 66.7% of patients after non-, onesided and bothsided nervesparing procedure were able to obtain sufficient erection for intercourse, respectively. Regarding quality of life, mean global health score according to QLQ-C30 was 69.4%. Conclusion HIFU treatment for localized prostate cancer shows acceptable oncological safety. Quality of life after HIFU is better than in the general population and ranges within those of standard treatment options compared to literature. HIFU seems a safe valuable treatment alternative for patients not suitable for standard treatment.